DEVELOPMENT OF DIGITAL MARKETING MANAGEMENT IN HOME INDUSTRY BUSINESS ACEH SOUVENIR ARTICLES IN MUARA BATU DISTRICT, ACEH UTARA DISTRICT - Ichsan; Ahmad Fauzul Hakim Hasibuan; Arliansyah; Hanif; Reza Juanda (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The souvenir business is a business that has been running in the Muara Batu sub-district, North Aceh district for several decades. Tourist interest in merchandise and souvenirs when visiting Aceh province, especially cross-coastal areas, is a special attraction when shopping. North Aceh is an administrative area with a district administration, Muara Batu sub-district is right in the middle of the eastern route of Sumatra. Located between Banda Aceh and Medan, this district is a vital distribution and trade route in Aceh. Unfortunately this has not been supported by the use of technology in fostering digital marketing management. The solution to partner problems is to develop business management, develop human resources, provide guidance on partner product promotion, motivating employees and mastery of technology. The program monitoring and evaluation system as well as seeing the impact of implementing the program was tested using the CIPP method. The outputs in this service are: 1. Draft Scientific Publications in Community Service Journals 2. Indonesian Serambi Mass Media Articles 3. Partner Capacity Building with Digital Marketing Optimization.